Using Personalized Recommendations in Artificial Intelligence to Increase Sales of Small Businesses in E-Commerce - Rohach, Yaroslav (Актуальні питання економічних наук, 2025)
Personalized recommendations in artificial intelligence are becoming increasingly relevant for increasing sales by small businesses in e-commerce due to escalating competition in online commerce and changing customer expectations. The growing consumer preference for personalized offers is weakening traditional marketing strategies. Although such systems have already proven to be effective at the scale of large enterprises, problems with access to huge amounts of data, economic resources, and technical knowledge prevent them from benefiting small businesses. The purpose of the article is to provide a theoretical and practical overview of the use of personalized recommendations in small e-commerce businesses, the effectiveness of the main methods of their implementation and the results of their use, and to identify barriers that prevent the external use of such systems when assessing their effectiveness. Methods: analysis of scientific literature, generalization, systematization. The results of the study show that the introduction of personalized recommendations in small business marketing campaigns increases revenue and provides a higher level of customer satisfaction. The use of artificial intelligence in recommendation systems triples the relevance of offers. This, in turn, has a positive impact on conversion and customer loyalty. On the other hand, the study revealed a number of problems faced by small companies today. These include a lack of quality data, difficult integration into existing business processes, and further compliance with GDPR requirements. The conclusions show that personalized recommendation systems based on artificial intelligence are one of the most promising tools for improving the efficiency of small businesses in the e-commerce sector. They help to create a unique approach to each customer, which, in turn, proves a competitive advantage for firms even with limited resources. However, maximum efficiency can be achieved only if the technological and organizational aspects of implementation and adaptation of personalization tools to the specifics of the company's activities are taken into account.